PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA POP-UP BOOK TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V MI MUHAMMADIYAH PEKALONGAN - Issa Virnama Della; Dayu Rika Perdana; Siti Nuraini; Mujiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem of this study is the lack of critical thinking skills of students in the Pancasila Education subject of grade V MI Muhammadiyah Pekalongan which is still in the sufficient category. This study aims to determine the effect of the use of the Problem Based Learning (PBL) model assisted by pop-up book media on students' critical thinking skills. This study uses a quantitative approach with a quasi-experimental design. The study population is all grade V students, with two classes as samples, namely the control class using Discovery Learning assisted by PPT and the experimental class using Problem Based Learning (PBL) assisted by pop-up book media. The results of the study indicate that there is an effect of the use of the Problem Based Learning (PBL) model assisted by pop-up book media on students' critical thinking skills.